An early Jesuit bibliographer, Pedro Ribandeneira - Doyle, John W. (John William), 1916- (1974)
The article is entitled: "An early Jesuit bibliographer: Pedro Ribandeneira". Also included are photocopies of various issues of "Schools Bulletin" (1968-1973) issued by the Jesuits.
Manuscript reference: NLA MS 4584.
Photocopy.
Originals in private ownership.
Keywords: Ribadeneyra, Pedro de, -- 1526-1611.; Jesuits -- Biography; Jesuits -- Education -- Australia -- Periodicals; Clergy